Analysis Analysis of the Influence of Corporate Governance and Digital Financial Innovation on Increasing MSME Income in Cemara Asri, Medan. : Analisis Pengaruh Tata Kelola Perusahaan dan Inovasi Keuangan Digital terhadap Peningkatan Pendapatan UMKM di Cemara Asri, Medan. - Carren; Deliyanti Simbolon (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to find out whether Corporate Governance and Digital Financial Innovation have a significant effect on increasing MSME Income in Cemara Asri, Medan. This study uses quantitative data methods and the data source is primary data. The population in this study is MSMEs that are polluted by Asri, which totals 52 MSMEs. Data analysis and testing consisted of validity tests, reliability tests, descriptive statistics, classical assumption tests, multiple regression analysis, partial hypothesis testing (t-test) and simultaneous tests (F tests), as well as determination coefficient tests. The results of the study show that Corporate Governance has a significant partial effect on the increase in MSME Income in Cemara Asri Medan with a calculated t value of 2,254 > ttable 2,009. Digital Financial Innovation has a significant partial effect on the Increase in MSME Income in Cemara Asri Medan with a calculated t value of 8,704 > ttable 2,009. Corporate Governance and Digital Financial Innovation have a simultaneous significant effect on the Increase in MSME Income in Cemara Asri Medan with an F value of 247,628 > Ftable 3.18 with a regression coefficient value of 91%.